Subjective Indicators - Beatrice Rammstedt (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Subjective indicators have been proven to possess predictive power for a large array of social and economic outcomes. However, most of these measures face serious psychometric shortcomings, namely that the items used are not psychometrically investigated. Further, for the assessment of one and the same construct various different item phrasing and response formats are used in different surveys. In the present paper several recommendations are made to increase the quality and by that also the acceptance and usage of subjective indicators. These include to develop more ultra-short but multi-item measures for subjective indicators. Further, surveys should try to use the same form of measurement, i.e. the same item phrasings and the same response scales. In terms of psychometric properties it is recommended to investigate reliability and validity of the indicators in as much depth as possible. In addition suggestions are made how to investigate the respondent's judgmental process for the subjective indicators' measures which allows to obtain a clearer picture of how the item is understood by the respondent and on which cues he bases his judgment.
Keywords: 330; subjective indicators; reliability; validity; multi-item instruments; cognitive interviews